A Generalized Approach to the Calculation Procedure of Distribution Network Steady-state and Transient Regime - Berzan V.; Postoronca Sv.; Vieru D.; Tintiuc Iu. (Problems of the Regional Energetics)
The low-voltage electrical distribution networks are characterized by ramified topology and spatial distribution of the consumers connected to the power supply. This leads to certain difficulties in calculation of such circuits even in the case of steady state mode, since even in stationary case a new separate problem must be solved each time. We have to mention that these difficulties are even more pronounced in the case of the circuit transient analysis. This paper proposes a generalized approach to calculation of steady-state and transient regimes in the branched distribution networks with RLC loads. To solve this problem we propose to use the mesh currents method, representation of the system of equations in matrix form and the Laplace transform. This gives the possibility to determine the characteristics of the current and voltage changes over time in the network and in the load. The difference between the obtained results and the known results, published in the open sources, is determined by the fact that the calculation of stationary and transient modes, is performed using the same calculations algorithm for both stationary and transient regimes.